Cyclic polymers revealing topology effects upon self-assemblies, dynamics and responses. Issue 38 (14th October 2015) - Yamamoto, Takuya; Tezuka, Yasuyuki
<x xml:space="preserve">Abstract</x> Unprecedented topology effects have been disclosed by new cyclic polymers upon their self-assemblies, dynamics and responses.